PENUMBUHAN BUDI PEKERTI BERBASIS KEARIFAN LOKAL MELALUI PEMBELAJARAN SASTRA ANAK PADA SISWA KELAS TINGGI DI SEKOLAH DASAR YOGYAKARTA - Anang Sudigdo (Universitas Ahmad Dahlan, 2018)
This research aims to describe: (1) intrinsic element in child literature can be implemented as a way of indigenous wisdom based on local wisdom upper class students at Yogyakarta state elementary school; (2) the values of character education in children's literature; (3) the process of child literature implementation as a way of character growth based on local wisdom in elementary school students in Yogyakarta. This research is done by qualitative method and content approach. The resulting conclusions are: (1) the children's literary intrinsic element which can be implemented as a way of character development based on local wisdom including theme, plot, figures, character, setting, point of view and moral value; (2) the story Children's Literature presented by the teacher in the classroom learning contains the values of character education and culture based; (3) teachers inculcate character education to students through Children's Literature that is folklore.